Distant Metastasis–Free Interval and Overall Survival in Breast Sarcoma: A Single-Institution Retrospective Study - Buta, Marko; Goran, Merima; Inic, Zorka; Santrac, Nada; Jeftic, Nikola; Raketic, Jovan; Pavlovic, Saska; Savkovic, Nevena; Zegarac, Milan; Stojiljkovic, Dejan; Cvetkovic, Ana; Stojanovic-Rundic, Suzana; et al. (Medical Research, 2026)
Background: Breast sarcomas (BS) are rare malignant tumors with aggressive behavior and limited evidence guiding outcome assessment. Data on distant metastasis–free interval (DMFI) in this population are scarce. This study aimed to describe oncologic outcomes and to explore clinicopathologic factors associated with DMFI and overall survival (OS) in patients with BS treated with curative intent.Methods: Patients with primary or secondary breast sarcoma treated at a single tertiary cancer center between 2013 and 2025 were retrospectively analyzed. Patients with metastatic disease at diagnosis were excluded. DMFI was the primary endpoint and OS was secondary. Survival was estimated using Kaplan–Meier methods and compared with log-rank tests. Exploratory receiver operating characteristic analyses were performed for descriptive stratification.Results: Twenty-six patients met inclusion criteria. Angiosarcoma was the most common histologic subtype, predominantly occurring as secondary disease after prior breast radiotherapy. Median DMFI was not reached during follow-up, with 71.5% of patients remaining metastasis free at 3 years, whereas median OS was 31 months with a 3-year OS of 46.9%. Shorter DMFI was associated with higher pathological T stage, larger tumors, tumor necrosis, younger age, and narrower resection margins. Overall survival was significantly associated only with resection margins, which was the sole variable related to both DMFI and OS. Exploratory Cox regression analyses were inconclusive because of limited event numbers.Conclusions: Tumor burden–related factors, tumor necrosis, and surgical margin width were associated with metastasis-related outcomes and survival in breast sarcoma. Adequate surgical resection remains critical in this rare and heterogeneous disease.
Keywords: Breast sarcoma; Distant metastasis–free interval; Overall survival; Surgical margins; Angiosarcoma